Introduction SWOT Analysis Method to Determining Security Improvement Strategies in RT 02 / RW XIII Buper Waena - Rumbiak (indoensia), Grace; Murwaniputri (indonesia), Hesti (JURNAL KASTARA, 2025)
ABSTRACT The existence of economic disparities has given rise to a city phenomenon, namely criminal acts such as theft, robbery and so on. As citizens, the unrest that arises due to this criminal act gives rise to proposals and recommendations to the local RT/RW administrators where the proposals given are very diverse so that in responding to the proposal an analysis technique is needed. A quick response to the unrest of the community in RT 002 / RW XIII Buper Waena must be followed up immediately because this RT/RW area is an area where criminal acts often occur, namely theft. The most common theft is theft of motor vehicles (Two Wheels). The purpose of this service is to determine the right strategy to find out the right stages to respond to existing security conditions. The method that will be introduced and become the content of this service is the introduction of the SWOT analysis method, where this analysis will consider existing internal and external factors. Internal factors consist of strengths (Strengths) and weaknesses (Weaknesses) while external factors are opportunities (Opportunities) and challenges (Threats). The calculation shows that the security enhancement strategy is in the X-axis quadrant with a value of -0.67 and the Y-axis with a value of 0.48 with a Cartesian quadrant model as in the image below shows that the security enhancement strategy is in quadrant III (ST).